Redesign of Qortoba School - Diala Issa; Emad Burghal; Mutaz Abu Zahra (My University, 2013)
Third Generation Green Schools:Redesign of Qortoba Secondary School:In the second graduation project, the trend was to redesign a constructed school according to the environmental standards.Qortoba secondary schools was selected by the supervisor which was hade many structural and environmental problems.The schools was visit by the teamwork to diagnose the problems that the schools suffering from, and each member of the team work specialized in a certain side of the diagnosing. many problems were founded and each one was studied by the site diagnosing and by the asking the users of the schools. Here was the beginning of the starting of the start of the second graduation project.Also, Ein Monjed school was visited by the teamwork which was green school, to evaluate the level reached by the ministry of education, and really they were reached to an advance level in designing of the green schools, buy unfortunately this level was reached without take into account the needed requirements in designing the green schools. And here also the issue of applying the systems of green schools in the new generation of the constructed new schools by the ministry of education was another issue to be studied in the second graduation project. The second Graduation Project was divided into four phases:The first phase was:         Diagnose the existed problems in the recently green schools constructed by the ministry of education: Site investigation was done b the team work to diagnose the existed problems, many problems appeared such as the use of green schools systems without take into account the requirements or the validity of applying these systems. For Example, acoustical panels were used for decorative purposes and reuse of grey water was used inefficiently. Also the use of shutters in the north elevationetc. In addition, structural problems on the both phase of designing phase and in the execution phase. Also, neglecting of the reinforcement details in the earthquakes design system.The second phase was:         Diagnose of existed problems in the non green schools and the possibility of greening or to reduce the effect of the non green phenomena.  Also, a site visit was hired by the team work members to many schools in the Palestinian cities , and also many problems were founded such as the bad architectural design .and the functionless design of the distribution of the spaces and zones, also the existence of the human comfort ,the high heat loss in winter, and bad ventilation of spaces, the waste of use the grey water etc   .All these problems were recognized by the teamwork and suggested solutions were decided to be used. The possibility of greening these schools was the milestone in our study , and many suggestions was suggested to carry out the possibility of greening theses schoolsThe third phase was: Redesign Qortoba school according to the standard and green systems considerations: The third phase was the most important one; and the trend was to redesign a constructed school to achieve two main purposes and to hit to birds by one stone.The first purpose was to redesign a green school from zero point according to the required standards and consideration. And the second purpose was to study the feasibility and the possibility of greening the constructed school. All sides of green schools systems were studied and we applied the possible and the useful one.Acoustical problems were studied and Ecotect software was used to evaluate the problems and the reverberation time analysis,and also manual calculation were hired to check the software results. Thermal problems were also evaluated and Ecotect was used in calculation the thermal loads and to show the difference after and before the operation of greening. Daylight analysis using Ecotect were conducted and many problems appeared as the non uniformity of the distribution of the daylight and the high or low level of the day light.And solutions were decided and other were suggested.  Artificial lighting analysis were conducted by Dialux software . Mechanical and electrical design also were hired and drawn according to its calculations.Architectural modification was done to avoid the potential problems could be appeared. Structural design using SAP were done and required execution planes were attached.  Earthquake resistant reinforcement details were taken into account in the design. Finally a presentation was prepared to show the results was presented.

Third Generation Green Schools:Redesign of Qortoba Secondary School:In the second graduation project, the trend was to redesign a constructed school according to the environmental standards.Qortoba secondary schools was selected by the supervisor which was hade many structural and environmental problems.The schools was visit by the teamwork to diagnose the problems that the schools suffering from, and each member of the team work specialized in a certain side of the diagnosing. many problems were founded and each one was studied by the site diagnosing and by the asking the users of the schools. Here was the beginning of the starting of the start of the second graduation project.Also, Ein Monjed school was visited by the teamwork which was green school, to evaluate the level reached by the ministry of education, and really they were reached to an advance level in designing of the green schools, buy unfortunately this level was reached without take into account the needed requirements in designing the green schools. And here also the issue of applying the systems of green schools in the new generation of the constructed new schools by the ministry of education was another issue to be studied in the second graduation project. The second Graduation Project was divided into four phases:The first phase was:         Diagnose the existed problems in the recently green schools constructed by the ministry of education: Site investigation was done b the team work to diagnose the existed problems, many problems appeared such as the use of green schools systems without take into account the requirements or the validity of applying these systems. For Example, acoustical panels were used for decorative purposes and reuse of grey water was used inefficiently. Also the use of shutters in the north elevationetc. In addition, structural problems on the both phase of designing phase and in the execution phase. Also, neglecting of the reinforcement details in the earthquakes design system.The second phase was:         Diagnose of existed problems in the non green schools and the possibility of greening or to reduce the effect of the non green phenomena.  Also, a site visit was hired by the team work members to many schools in the Palestinian cities , and also many problems were founded such as the bad architectural design .and the functionless design of the distribution of the spaces and zones, also the existence of the human comfort ,the high heat loss in winter, and bad ventilation of spaces, the waste of use the grey water etc   .All these problems were recognized by the teamwork and suggested solutions were decided to be used. The possibility of greening these schools was the milestone in our study , and many suggestions was suggested to carry out the possibility of greening theses schoolsThe third phase was: Redesign Qortoba school according to the standard and green systems considerations: The third phase was the most important one; and the trend was to redesign a constructed school to achieve two main purposes and to hit to birds by one stone.The first purpose was to redesign a green school from zero point according to the required standards and consideration. And the second purpose was to study the feasibility and the possibility of greening the constructed school. All sides of green schools systems were studied and we applied the possible and the useful one.Acoustical problems were studied and Ecotect software was used to evaluate the problems and the reverberation time analysis,and also manual calculation were hired to check the software results. Thermal problems were also evaluated and Ecotect was used in calculation the thermal loads and to show the difference after and before the operation of greening. Daylight analysis using Ecotect were conducted and many problems appeared as the non uniformity of the distribution of the daylight and the high or low level of the day light.And solutions were decided and other were suggested.  Artificial lighting analysis were conducted by Dialux software . Mechanical and electrical design also were hired and drawn according to its calculations.Architectural modification was done to avoid the potential problems could be appeared. Structural design using SAP were done and required execution planes were attached.  Earthquake resistant reinforcement details were taken into account in the design. Finally a presentation was prepared to show the results was presented.
Redesign of Qortoba School